Pengaruh Metode Show and Tell Terhadap Keterampilan Berpidato Dengan Tema Sumpah Pemuda Siswa Kelas V SDN Rejosari - HN, Ganesa Marta Sasmita; Destiniar, Destiniar; Selegi, Susanti Faipri (ANTHOR: Education and Learning Journal, 2022)
This study aims to determine the effect of the show and tell method on speech skills with thetheme of the youth oath of class V SDN Rejosari. The research method used is an experimental method with a one-group pretest-posttest design. The population taken is all students of class V, totaling 26 students. Data collection techniques in this study were performance tests and documentation. The data analysis technique used the t test with a significant level of = 0.05. It was concluded that there was an effect of the showand tell method on speech skills with the theme of the youth oath of fifth grade students at SDN Rejosari. Based on the calculation, the posttest mean value is greater than the pretest average value. Thus the show and tell method can improve the speaking skills of fifth grade students at SDN Rejosari.